2001
DOI: 10.1093/neuonc/3.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of stereotactic biopsy in the initial management of gliomas

Abstract: Stereotactic biopsy is often performed for diagnostic purposes before treating patients whose imaging studies highly suggest glioma. Indications cited for biopsy include diagnosis and/or the "inoperability" of the tumor. This study questions the routine use of stereotactic biopsy in the initial management of gliomas. At The University of Texas M. D. Anderson Cancer Center, we retrospectively reviewed a consecutive series of 81 patients whose imaging studies suggested glioma and who underwent stereotactic biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
139
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(149 citation statements)
references
References 1 publication
4
139
0
6
Order By: Relevance
“…There were 19 studies identified using craniotomy [3,4,7,9,10,11,12,32,33,34,35,36,37,38,39,40,41,42,43]. Of these, 6 articles were excluded [3,32,37,42,43] due to an inability to break out complications related to surgery in areas of eloquence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 19 studies identified using craniotomy [3,4,7,9,10,11,12,32,33,34,35,36,37,38,39,40,41,42,43]. Of these, 6 articles were excluded [3,32,37,42,43] due to an inability to break out complications related to surgery in areas of eloquence.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 6 articles were excluded [3,32,37,42,43] due to an inability to break out complications related to surgery in areas of eloquence. Additionally, one article was excluded [12] due to the assumption that these patients were reported on in Kim et al [33] and to reduce the chance of double counting. Online supplementary Appendix 2 shows the craniotomy studies included (total of 12 craniotomy studies included).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These confounding factors may compromise treatments, so a biopsy is usually performed, but it is an invasive procedure and therefore risks are involved. Also, grading of gliomas, a notoriously inhomogeneous type of tumor, has many confounding factors, to the point that approximately 38% of stereotactic biopsy diagnosis may differ from histopathological classification performed in resections from the same patient (Jackson et al, 2001). Brain tumor diagnosis would benefit much from an automated analysis of MR spectra due to these factors, helping to improve the accuracy of the radiological findings.…”
Section: Introductionmentioning
confidence: 99%